Seoul Train - Butterworth, Jim; Lubarsky, Aaron; Sleeth, Lisa (United States : Sleeth, Lisa ; Butterworth, Jim, 2004)
With its riveting footage of a secretive underground railroad, "Seoul Train" is the gripping documentary exposé into the life and death of North Koreans as they try to escape their homeland and China. The film also delves into the complex geopolitics behind this growing and potentially explosive humanitarian crisis. By combining vérité footage, personal stories and interviews with experts and government officials, "Seoul Train" depicts the flouting of international laws by major countries, the inaction and bureaucracy of the United Nations, and the heroics of activists that put themselves in harm's way to save the refugees.
Duration: 00:54:00
Keywords: Documentary films